Representasi Keragaman Budaya dalam Serial Never Have I Ever Season 1 - Tedi Supendi, Alya Nurjannah (PT. Alahyan Publisher Sukabumi, 2023)
The cultural diversity in the film Never Have I Ever Season 1 is very interesting to analyze. This research is a cross-cultural understanding research with a qualitative approach. Data is taken via the internet on the Netflix streaming platform. By applying Hall's representation theory, this research examines how cultural diversity is represented in drama series. This research also explains how cross-cultural understanding is displayed in the drama series and what ideologies the author wants to convey to society. The results of this research show that cultural diversity is not only seen in the language, clothing, customs, and typical food of each region. However, the cultural diversity displayed is the presence of Indian culture entering and mingling in America. The ideology that the author wants to convey is how cultural diversity must be addressed with awareness and tolerance to build unity and create a harmonious life to avoid conflict between certain individuals or groups.